(untitled) (IJM: Journal of Multidisiplinary, 2024)
Indonesia is a country that is rich in diversity so that social contact makes it easier for there to be friction between groups or factions and between religious adherents. This research uses a descriptive qualitative approach. The data sources that researchers use are primary and secondary data, primary data sources come from school principals, teachers, students while the primary data source comes from documentation. The collection process in this research uses three techniques, namely; participatory interviews, interviews and documents. The data analysis technique goes through the stages of data collection, condensation, data display, drawing conclusions. The results of this research are: First, planning religious moderation towards students' religious attitudes at SMP Negeri 03 Colomadu including: Student selection, indoctrination, instrumentation. Second, implementing religious moderation towards students' religious attitudes at SMP Negeri 03 Colomadu includes; attitudes of tolerance, non-bigotry group, respecting culture, prioritizing unity. Third, evaluation of religious moderation on students' religious attitudes at SMP Negeri 03 Colomadu includes: changing attitudes, improving knowledge and increasing skills.